Study of associated factors with risk of fall in frail older patients - Tam, Nguyen Ngoc; Trung Anh, Nguyen (Tạp chí Nghiên cứu Y học, 2025)
The frailty syndrome and fall risk go hand in hand in the ageing process, significantly affecting the quality of life in elderly patients. The purpose of this study was to explore factors related to fall risk in older patients with frailty syndrome. A cross-sectional study of older frail patients was conducted, at the National Geriatric Hospital. All patients were diagnosed as having frailty by using Freid’s criteria. Factors associated with fall risk of older frail patients are age (greater or equal to 80 years old) (OR = 2.315), polypharmacy (OR = 2.784), depression (OR = 3.718), IADLs dependence (OR = 4.589), risk of malnutrition (OR = 2.089), lower limb strength (OR = 2.807) and cognitive impairment (OR = 4.559). An effective multidisciplinary strategy to prevent and reduce fall risks for older people having frailty is necessary, including intervention on polypharmacy, depression, dependences, malnutrition, low physical performance and cognitive impairments.